Sex Differences in the Patterns of Systemic Agent use Among Patients With Psoriasis: A Retrospective Cohort Study in Quebec, Canada - Milan, Raymond; LeLorier, Jacques; Brouillette, Marie-Josée; Holbrook, Anne; Litvinov, Ivan V.; Rahme, Elham (Frontiers in Pharmacology, 2022)
Background: Sex differences exist in psoriasis manifestation and expectations from treatment with systemic agents, including, conventional systemic agents (CSA) and tumor necrosis factor inhibitor or ustekinumab (TNFi/UST). However, sex differences in patterns of systemic agent use, such as CSA discontinuation and switch from CSA to TNFi/UST have not been examined. Objectives: To assess sex differences in patterns of CSA use and identify factors associated with switch to (or add) a TNFi/UST and those associated with CSA discontinuation. Methods: We conducted a retrospective cohort study using the Quebec health administrative databases. We included patients with psoriasis initiating a CSA in 2002-2015. We excluded patients with a psoriasis diagnosis in the three years prior to the first diagnosis date between 2002 and 2015, and those with a systemic agent dispensation in the year prior to that date. We used Cox regression models with the LASSO method to identify factors associated with switch/add TNFi/UST, and those associated with CSA discontinuation. Separate analyses were performed for male and female patients. Results: We included 1,644 patients, among whom 60.4% discontinued their CSA and 7.4%, switched/added TNFi/UST within a median of 0.78 years of follow-up. Obesity in male patients (3.53, 1.20-10.35), and adjustment/somatoform/dissociative disorders (3.17, 1.28-7.85) and use of NSAIDS (2.70, 1.56-4.70) in female patients were associated with switch/add TNFi/UST. Male patients followed by a rheumatologist (0.66, 0.46-0.94) and those with a prior hospitalization (0.70, 0.57-0.87) were at lower risk of CSA discontinuation, while those initiated on acitretin (vs methotrexate) were at higher risk to discontinue their CSA (1.61, 1.30-2.01). Female patients with rheumatoid arthritis comorbidity (0.69, 0.51-0.93), those with a dispensed lipid-lowering agent (HR 0.72, 95% CI 0.59-0.88) and hypoglycemic agent (0.75, 0.57-0.98) and those initiated on methotrexate were less likely to discontinue their CSA. All patients entering the cohort between 2011 and 2015 were at reduced risk of CSA discontinuation. Conclusion: Most male and female patients discontinued their CSA within 1 year of follow-up. Our study highlighted sex differences in patients’ characteristics associated with switch/add a TNFi/UST and CSA discontinuation; treatment switch and discontinuation may be indications of treatment failure in most patients.